A survey of manufacturing oriented topology optimization methods. (October 2016) - Liu, Jikai; Ma, Yongsheng
Highlights: Presents a survey of manufacturing oriented topology optimization methods. Investigates the length scale control and geometric feature based design for machining oriented topology optimization. Investigates the part ejection and rib thickness control for injection molding/casting oriented topology optimization. Proposes the future research direction for additive manufacturing oriented topology optimization. Abstract: Topology optimization is developing rapidly in all kinds of directions; and increasingly more extensions are oriented towards manufacturability of the optimized designs. Therefore, this survey of manufacturing oriented topology optimization methods is intended to provide useful insight classification and expert comments for the community. First, the traditional manufacturing methods of machining and injection molding/casting are reviewed, because the majority of engineering parts are manufactured through these methods and complex design requirements are associated. Next, the challenges and opportunities related to the emerging additive manufacturing (AM) are highlighted. SIMP (Solid Isotropic Material with Penalization) and level set are the concerned topology optimization methods because the majority of manufacturing oriented extensions have been made based on these two methods.